Increasing our understanding of dying of breast cancer: Comorbidities and care. (3rd May 2016) - Johnston, G.M.; Urquhart, R.; Lethbridge, L.; MacIntyre, M.
Abstract : Background : Screening and treatment for breast cancer have improved. However, attention to palliative support and non-cancer co-morbidities has been limited. This study identified types of care for and co-morbidities of persons dying of breast cancer compared to persons dying from all cancers and from non-cancer causes. Methods : Linked administrative data from population-based registries were used to examine 121, 458 deaths in Nova Scotia from 1995 to 2009. Results : Breast cancer decedents' mean age was similar to that of all cancer decedents (72.0 versus 72.1 years), but their age spread was greater (20–59 years: 23.1% versus 16.7%; 90+ years: 11.2% versus 6.5%). Among women dying of breast cancer, 15.6% were enrolled in the diabetes registry and 15.1% in the cardiovascular registry, indicating that they had these non-cancer conditions prior to their death. Compared to all cancer decedents, breast cancer decedents were twice as likely to have dementia as a cause of death, and were less likely to die in hospital but more likely to die in a nursing home. Breast cancer decedents had place of death rates more similar to non-cancer than cancer decedents. Conclusions : Rates of dementia and diabetes among the breast cancer decedents were particularly note-worthy in this novel study given that these comorbidities have not received much attention in the breast cancer research literature. Further collaboration with non-cancer disease programs is advised. The extent of adequate comprehensive palliative support for the 20% of the breast cancer decedents who are nursing home residents requires investigation.